V.1 - Sengar, Shailendra (New Delhi, 2007)
Indian culture is rich and diverse and as a result unique in its very own way.? Our manners, way of communicating with one another, etc. are one of the important components of our culture.? Even though we have accepted modern means of living, improved our lifestyle, our values and beliefs still remain unchanged.? In this comprehensive attempt we present exhaustive and elaborate details about various civilisations, cultures, myths, Gods, faiths, religions, art, music, dance, paintings, architecture, literature, and many more aspects of Indian society-ancient, medieval, as well as modern.
Keywords: Culture-India